Amplification of the Ocean Carbon Sink During El Niños: Role of Poleward Ekman Transport and Influence on Atmospheric CO2. Issue 9 (8th September 2020) - Liao, Enhui; Resplandy, Laure; Liu, Junjie; Bowman, Kevin W.
Abstract: Amplification of the ocean carbon sink during El Niño events partially offset terrestrial biosphere carbon losses to the atmosphere, but uncertainties in the magnitude, timing, and spatial extent of the ocean response confound our understanding of the global carbon budget and its sensitivity to climate. Here, we examine the mechanisms controlling the anomalous tropical Pacific Ocean CO2 drawdown during El Niño events harnessing multidecadal ocean pCO2 observations in conjunction with a state‐of‐the‐art ocean biogeochemical model. We show that poleward Ekman transport dramatically amplifies the near‐equatorial pCO2 anomaly identified in prior work and that this amplification varies considerably between El Niño events. During central Pacific events, the CO2 flux anomaly can vary up to fourfold between events (2002/2003 vs. 2015/2016), but it always recedes during the boreal winter to spring transition and the poleward transport of the anomaly mostly extends into the Northern Hemisphere. During eastern Pacific events characterized by an equatorially centered intertropical convergence zone (e.g., 1997/1998), the intense CO2 flux anomaly persists into boreal summer and can extend further into the Southern Hemisphere. The hemispheric asymmetry (northward vs. southward extension) and the termination (boreal winter/spring for central Pacific events vs. boreal summer for eastern Pacific events) of the ocean CO2 response are tied to the El Niño dynamics in the near‐equatorial region and also how it is amplified by poleward Ekman transport. Finally, we evaluate how differences in the ocean response influence atmospheric CO2 and discuss the potential of atmospheric CO2 satellite data to provide observational constraints. Key Points: Anomalous ocean CO2 drawdown originated from near‐equatorial Pacific Ocean during El Niño is amplified by poleward Ekman transport Equatorially centered ITCZ during extreme eastern Pacific El Niño events yields a more intense and long‐lasting ocean CO2 drawdown Atmospheric CO2 satellite data could constrain spatiotemporal differences in CO2 drawdown between events